Potential tolerability of ancient grains in non-celiac wheat sensitivity patients: A preliminary evaluation - Seidita, Aurelio; Mansueto, Pasquale; Giuliano, Alessandra; Chiavetta, Marta; Mandreucci, Francesca; Soresi, Maurizio; Pistone, Mattia; Compagnoni, Stella; Castellucci, Daniele; Bisso, Gianluca; Faraci, Francesco; Maestri, Salvatore; et al. (Frontiers in Medicine, 2022)
Background & Aims: wheat-free diet (WFD) represents the elective treatment for Non-Celiac Wheat Sensitivity (NCWS) patients. Preliminary reports have shown a possible better tolerability of ancient grains in these subjects. The aim of this study is to evaluate the frequency of consumption of ancient grains and its correlation with clinical manifestations in NCWS patients. Methods: 223 NCWS patients were recruited, and consumption of ancient grains and their varieties was monitored. Participants were first administered a modified version of the Pavia/Biagi questionnaire to investigate their adherence to “modern WFD”. The appearance/exacerbation of symptoms after ingestion of ancient grains was then assessed with WHO toxicity grading scale. Results: 50.2% of the recruited patients reported consuming ancient grains before NCWS diagnosis; the diagnostic delay in this group was significantly higher than in non-consumers [median (range) 72 (6-612) vs 60 months (3-684), P=0.03] and these patients reported lower frequency of constipation (P=0.04). Of the 107 patients with optimal adherence to modern WFD, 14 reported eating ancient wheat after NCWS diagnosis. Among them, 5 reported milder symptoms than those caused by modern wheat intake and 3 had an excellent tolerability without symptoms. Timilia/Tumminia variety was the most frequently used ancient grain. Conclusions: NCWS patients who consume ancient grains may receive a late diagnosis due to the possible clinical benefit (tolerability) obtained with these grains. Even after diagnosis, 10% of the patients still consumed ancient grains and had mild or no symptoms. Further studies are required to define the pathophysiological mechanism behind their putative greater tolerability.